Thyroid cytopathology: updates and molecular testing - Vance, J.; Gilani, S.M. (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2019)
The utility of fine needle aspiration (FNA) is well described in the context of evaluating thyroid lesions. Among the various international systems of classification of thyroid cytology, the Bethesda System for Reporting Thyroid Cytopathology (TBSRTC) has also provided a sound framework to standardize the reporting of FNA cytology results. New molecular evidence and clinical studies demonstrated the need for revision of the nomenclature resulting in introduction of new categories, such as the noninvasive follicular thyroid neoplasms with papillary-like nuclear features (NIFTP). Indeterminate thyroid cytology results pose a challenge for further management and the continued development of molecular markers may aid in the management of indeterminate thyroid lesions.